2008
DOI: 10.1007/s10342-008-0239-1
|View full text |Cite
|
Sign up to set email alerts
|

Influence of light availability on growth, leaf morphology and plant architecture of beech (Fagus sylvatica L.), maple (Acer pseudoplatanus L.) and ash (Fraxinus excelsior L.) saplings

Abstract: In a field study, we measured saplings of beech, ash and maple growing in a fairly even-aged mixed-species thicket established by natural regeneration beneath a patchy shelterwood canopy with 3-60% of above canopy radiation reaching the saplings. Under low light conditions, maple and ash showed a slight lead in recent annual length increment compared with beech. With increasing light, ash and maple constantly gained superiority in length increment, whereas beech approached an asymptotic value above 35% light. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
63
1
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 130 publications
(92 citation statements)
references
References 35 publications
12
63
1
2
Order By: Relevance
“…Under limiting light conditions, diameter increment of Douglas fir saplings in our study responded to trenching not as responsive as length increment. This agrees with a frequently observed characteristic of many less shade-tolerant species tending to invest preferentially into height growth rather than into lateral growth and by this increasing the chance to reach the forest canopy more quickly (Chen 1997;Chen and Klinka 1998;Petritan et al 2009). …”
Section: Interspecific Differences In Growth Responsesupporting
confidence: 77%
See 1 more Smart Citation
“…Under limiting light conditions, diameter increment of Douglas fir saplings in our study responded to trenching not as responsive as length increment. This agrees with a frequently observed characteristic of many less shade-tolerant species tending to invest preferentially into height growth rather than into lateral growth and by this increasing the chance to reach the forest canopy more quickly (Chen 1997;Chen and Klinka 1998;Petritan et al 2009). …”
Section: Interspecific Differences In Growth Responsesupporting
confidence: 77%
“…Of the environmental factors governing the growth conditions in the understorey, light is considered the most important factor (Kimmins 1997) and therefore has been widely investigated (inter alia Röhrig 1967;Kobe et al 1995;Kunstler et al 2005;Stancioiu and O'Hara 2006;Petritan et al 2007Petritan et al , 2009). On the other hand, the influence of overstorey root competition on growth of underplanted seedlings remains poorly investigated and understood (Coomes and Grubb 2000), although some studies found a strong below-ground competition between overstorey and understorey vegetation for water and nutrients (Christy 1986;McCune 1986;Riegel et al 1992;Walters and Reich 1997;Wagner 1999;Lindth et al 2003;Machado et al 2003).…”
mentioning
confidence: 99%
“…This effect is not illustrated in the literature for herbaceous or shrubby species, but it can be placed in parallel with results observed on tree response to light availability. Numerous studies have shown that the stem height / diameter ratio of trees decreases with light availability, suggesting that shade affects stem diameter growth more negatively than it does height growth (Petritan et al, 2009). For shadeintolerant species, a height increment can even occur in response to shade, in a "shade-avoidance reaction", corresponding to a height increment added to potentially seek more light (Dehlin et al, 2004).…”
Section: Vegetation Morphology In Response To Light Availabilitymentioning
confidence: 99%
“…Leaf area also infl uences the amount of diffuse light, which is a good predictor of plant growth (Jarčuška, 2011). Light availability can explain growth; shade-tolerant species can survive long periods in deep shade by greatly reducing their growth in height (Petriţan et al, 2008). Growth responses in individual plants are diffi cult to predict because the factors involved are numerous.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, light plays an outstanding role in forests, at least on mesic sites in temperate regions, and it can easily be manipulated by silvicultural treatments (Petriţan et al, 2008).…”
Section: Introductionmentioning
confidence: 99%